Plasma protein C levels are directly associated with better outcomes in patients with severe burns. Issue 7 (November 2019) - Lang, Thomas Charles; Zhao, Ruilong; Kim, Albert; Wijewardena, Aruna; Vandervord, John; McGrath, Rachel; Fitzpatrick, Siobhan; Fulcher, Gregory; Jackson, Christopher John
Highlights: Among 86 patients with severe burns, higher plasma protein C levels on admission to hospital were directly associated with better clinical outcomes. Smaller burn size, partial thickness burns and a lower neutrophil count on admission were also associated with better clinical outcomes. Plasma protein C may be a useful biomarker of burn severity. Abstract: Protein C circulates in human plasma to regulate inflammation and coagulation. It has shown a crucial role in wound healing in animals, and low plasma levels predict the presence of a wound in diabetic patients. However, no detailed study has measured protein C levels in patients with severe burns over the course of a hospital admission. A severe burn is associated with dysfunction of inflammation and coagulation as well as a significant risk of morbidity and mortality. The current methods of burn assessment have shortcomings in reliability and have limited prognostic value. The discovery of a biomarker that estimates burn severity and predicts clinical events with greater accuracy than current methods may improve management, resource allocation and patient counseling. This is the first study to assess the potential role of protein C as a biomarker of burn severity. We measured the plasma protein C levels of 86 patients immediately following a severe burn, then every three days over the first three weeks of a hospital admission. We also analysed the relationships between burn characteristics, blood test results including plasma protein C levels and clinical events. We used a primary composite outcome of increased support utilisation defined as: a mean intravenous fluid administration volume of five litres or more per day over the first 72 h of admission, a length of stay in the intensive care unit of more than four days, or greater than four surgical procedures during admission. The hypothesis was that low protein C levels would be negatively associated with increased support utilisation. At presentation to hospital after a severe burn, the mean plasma protein C level was 76 ± 20% with a range of 34–130% compared to the normal range of 70–180%. The initial low can be plausibly explained by impaired synthesis, increased degradation and excessive consumption of protein C following a burn. Levels increased gradually over six days then remained at a steady-state until the end of the inpatient study period, day 21. A multivariable regression model (Nagelkerke's R 2 = 0.83) showed that the plasma protein C level on admission contributed the most to the ability of the model to predict increased support utilisation (OR = 0.825 (95% CI = 0.698-0.977), P = 0.025), followed by burn size (OR = 1.252 (95% CI = 1.025–1.530), P = 0.027), burn depth (partial thickness was used as the reference, full thickness OR = 80.499 (1.569–4129.248), P = 0.029), and neutrophil count on admission (OR = 1.532 (95% CI = 0.950–2.473), P = 0.08). Together, these four variables predicted increased support utilisation with 93.2% accuracy, 83.3% sensitivity and 97.6% specificity. However if protein C values were disregarded, only 49.5% of the variance was explained, with 82% accuracy, 63% sensitivity and 91.5% specificity. Thus, protein C may be a useful biomarker of burn severity and study replication will enable validation of these novel findings.